Photocatalytic and adsorption performance of faceted cuprous oxide (Cu2O) - Ho, Jeffrey Weng Chye (2016)
Cu2O particles of various facets were successfully synthesized via wet chemical methods; these included the cubic shaped particles with {100} facets, octahedral shaped {111} facets, rhombic dodecahedral shaped {110} facets and the truncated polyhedral particles with exposed {100}, {111} and {110} facets. In addition, spherical Cu2O with no specific facets was also synthesized. In this thesis, the adsorption capability and the photocatalytic performance were determined to understand the physical and chemical properties of Cu2O. The adsorption performance of the Cu2O particles in methyl orange (MO) solution is likely due to the difference in the surface charges. The MO, which is an anion dye, were attached to the positively charge surface of the Cu2O particles via electrostatic attraction. Among the faceted Cu2O particles, the octahedral shaped Cu2O was found to adsorb more anions probably due to the highest surface charges it possesses, which ranged from 19.7 to 33.0 mV. The adsorption kinetic of the octahedral shaped Cu2O was also studied; the adsorption equilibrium was calculated to be 96.42 mg/g following the Langmuir model, which indicates monolayer adsorption. Several observations were concluded in the photocatalytic performance of the faceted Cu2O particles. Firstly, the Cu2O of spherical shaped did not possess any photocatalytic activity. This could be due to the agglomeration of nanoparticles that potentially hinder the photocatalytic active sites. Secondly, series of experiments have been carried out to prove that cubic shaped Cu2O was indeed visible light active. Thirdly, compared to the rest of the Cu2O samples, Cu2O particle with the octahedral shape was observed to perform better in dye degradation under visible light irradiation. This might be because of the oxidation band potentials of the octahedral shaped Cu2O (+0.727 eV) particles which lie below of the MO solution (+0.711 eV) and thus, the photogenerated electron-hole pairs could be efficiently used to degrade the MO solution effectively. For the rest of the samples (cubic (+0.597 eV), rhombic dodecahedral (+0.547 eV) and truncated polyhedral (+0.537eV)) whose oxidation band potentials lie above MO, only the photogenerated electron was consumed during the dye degradation process. As such, it might slow down the entire photocatalytic processs. Lastly, the stability of Cu2O particles under solar light irradation was accessed. It was observed that the precipitates that formed on the surface of the Cu2O particles were mainly Cu(OH)2 nanoparticles and CuO. The photocorrosion products produced during dye degradation hinder the photocatalytic activity of Cu2O. The addition of methanol solution, a well-known hole scavenger, has shown to have alleviated the corrosion attack on Cu2O. This indicates that the photocatalytically generated holes were responsible for the photocorrosion of Cu2O. In order to prolong the stability of Cu2O, it is therefore necessary to have hole scavengers such as methanol to suppress the photocorrosion.